Laparoscopic repair of bladder rupture in a neonate. (15th April 2016) - Oki, Satoshi; Inoue, Mikihiro; Otake, Kohei; Matsushita, Kohei; Koike, Yuhki; Uchida, Keiichi; Kusunoki, Masato
Abstract: Bladder rupture in a fetus is a rare occurrence. We report the first neonatal case of laparoscopic repair for prenatally diagnosed bladder rupture. A male neonate, who had presented with megacystis, bilateral hydronephrosis and hydroureters since 27 weeks‐of‐gestation, was delivered by emergency cesarean section because of sudden collapse of the bladder with massive ascites at 37 weeks‐of‐gestation. The diagnosis of bladder rupture was made by retrograde urethrocystography. Laparoscopic repair was carried out subsequent to urethral catheterization. Intraoperatively, laceration from the left side of the bladder dome to the posterior wall was observed. This tear was successfully repaired using a two‐layer interrupted suture without any postoperative complications. Laparoscopic repair could be the treatment of choice for bladder rupture, because it has the advantage of closure of the perforated site more certainly than bladder decompression alone, and with better cosmesis than open repair.